SOCIO -ECONOMIC CONDITION SOCIO-CULTURE PRACTICE AND HEALTH AILMENTS OF RURAL WOMEN COMMUNITY USING BIOMASS FUEL - SINGH, ANAMIKA; KUMARI, REETA (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2021)
In this article the study was carried to review the past work done on the biomass fuel smoke and their adverse effect on the health of their users. Biomass fuel is long known factor for pollution and health ailments. Previously Most of the work in this area were found to be focused on respiratory health, eye disease and other health problems like asthma, tuberculosis, COPD, cataract, low birth weight and even cancer. Cigarette smoking and health ailments were found to be on the priority by researchers. Animal rearing is the complementary activity of farming for countryside citizens. Preparation of cow dung cake has been found to be the socioculture practice. Use of easily available natural fuel has been noticed as the old natural social trends regardless the awareness of ill impact on their health. In current study the health status of rural women has been investigated considering their economic condition and the socioculture practice also. Hematological and immunological parameters were selected to study for health status assessment.